2015
DOI: 10.1017/s0031182014001929
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and subtyping ofGiardiaandCryptosporidiumisolates from commensal rodents in China

Abstract: Cryptosporidium and Giardia are two important zoonotic intestinal parasites responsible for diarrhoea in humans and other animals worldwide. Rodents, as reservoirs or carriers of Cryptosporidium and Giardia, are abundant and globally widespread. In the present study, we collected 232 fecal specimens from commensal rodents captured in animal farms and farm neighbourhoods in China. We collected 33 Asian house rats, 168 brown rats and 31 house mice. 6.0% (14/232) and 8.2% (19/232) of these rodents were microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 51 publications
3
51
1
2
Order By: Relevance
“…Interestingly, despite abundant reports of infections in flies with other protozoa, such as Giardia duodenalis and Cryptosporidium spp. (Fetene et al 2011;Szostakowska et al 2004;Zhao et al 2014Zhao et al , 2015, there are no previously published studies regarding E. bieneusi in flies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, despite abundant reports of infections in flies with other protozoa, such as Giardia duodenalis and Cryptosporidium spp. (Fetene et al 2011;Szostakowska et al 2004;Zhao et al 2014Zhao et al , 2015, there are no previously published studies regarding E. bieneusi in flies.…”
Section: Discussionmentioning
confidence: 99%
“…), Mice ( Mus sp. ), Greater bilblies ( Macroties lagotis ), Girrafes house mice ( Mus musculus ), Eastern grey squirrel ( Sciurus carolinensis ), Golden hamster ( Mesocricetus auratus ), Rock hyrax ( Procavia capensis ), Large footed mouse-eared bat ( Myotis adversus ), Japanese field mouse ( Apodemus argenteus ), Bilbies ( Macrotis lagotis ), Bank voles ( Clethrionomys glareolus ), Campbell hamster ( Phodopus campbelli ), Siberian hamster ( Phodopus sungorus ), Golden hamster ( Mesocricetus auratus ), Mountain goats ( Oreamnos americanus ), Cynomolgus monkeys ( Macaca fascicularis ), East African mole rat ( Tachyoryctes splendens ), Ringed seal ( Pusa hispida ), Donkey ( Giraffa camelopardalis ), Ringed seal ( Phoca hispida ), Large Japanese field mouse ( Apodemus speciosus ), Cynomolgus monkey ( Macaca fascicularis ), Slow loris ( Nycticebus coucang ), Ostriches ( Struthio camelus ), Mountain gorillas ( Gorilla beringei beringei ), Asian house rat ( Rattus tanezumi ), Brown rat ( Rattus norvegicus ), House mouse ( Mus musculus )Numerous reports in humansChalmers et al., 1997, Hurkova et al., 2003Dubey et al., 2002, Morgan et al., 1999a, Xiao et al., 2002a, Xiao et al., 2004b, Warren et al., 2003, Nakai et al., 2004, Hikosaka and Nakai, 2005, Santín et al., 2005, Azami et al., 2007, Brikan et al., 2008, Kváč et al., 2008, Lupo et al., 2008, Lv et al., 2009, Kodádková et al., 2010, Feng, 2010, Murakoshi et al., 2013, Yang et al., 2011, Yang et al, 2013; Ng-Hublin et al., 2013, Karim et al., 2014, Qi et al., 2014, Sak et al., 2014, Du et al., 2015, Laatamna et al., 2015, Petrincová et al, 2015, Zhao et al., 2015b C. andersoni Bacterian camel ( Camelus bactrianus ), European wisent ( Bison bonasus ), Marmots Campbell hamster ( Phodopus campbelli ), Golden hamster ( Mesocricetus auratus ), Golden takins ( Budorcas taxicolor bedfordi ), Giant panda ( Ailuropoda melanoleuca ), Macaca mulatta ( Rhesus macaque ), American mink ( Mustela vison )MinorMatsubayashi et al., 2005, Wang et al., 2008, Lv et al., 2009, Stuart et al., 2013, Du et al., 2015, Wang et al., 2015, Zhao et al., 2015a C. felis Rhesus macaques ( Macaca mulatta ); Pallas's cat ( Felis Manul )Numerous reports in humansLucio-Forster et al., 2010, Ye et al., 2012, Bes...…”
Section: Wildlife Associated Outbreaks and Water Contaminationmentioning
confidence: 99%
“…Xiao et al, 2002;Leoni et al, 2006;Cama et al, 2007;Wang et al, 2013;Bodager et Lv et al, 2009;Wang et al, 2012 Numerous reports. Leoni et al, 2006;Morse et al, 2007;Waldron et al, 2011;Agholi et al, 2013;Jiang et al, 2014;Liu et al, 2014;Hussain et al, Chalmers et al, 1997;Matsui et al, 2000;Torres et al, 2000;Perz and Le Blancq, 2001;Bajer et al, 2003;Lv et al, 2009;Ng-Hublin et al, 2013;Qi et al, 2105;Zhao et al, 2015;Li et al, 2016 Commonly reported in humans…”
Section: Discussionmentioning
confidence: 99%
“…Guinea pigs Guinea pig (Cavia porcellus), California ground squirrels (Spermophilus beecheyi) Vetterling et al, 1971;Chrisp et al, 1990;Spano et al, 1997;Lv et al, 2009 No reports in humans to date Chalmers et al, 1997;Torres et al, 2000;Hurkova et al, 2003;Hikosoka et al, 2005;Ziegler et al, 2007;Kváč et al, 2008;Lv et al, 2009;Murakoshi et al, 2013;Ng-Hublin et al, 2013;Song et al, 2015;Zhao et al, 2015 Many reports - Gatei et al, 2006;Leoni et al, 2006;Muthusamy et al, 2006;Azami et al, 2007;Al-Brikan et al, 2008;Neira et al, 2012;Hasajová et al, 2014;Petrincová et al, 2015;Spanakos et al, 2015 Beaver genotype Rodents North American beaver (Castor canadensis) Feng et al, 2007 No Jiang et al, 2005;Feltus et al, 2006;Feng et al, 2007;Kváč et al, 2008;Insulander et al, 2013;Lebbad et al, 2013;Guo et al, 2015;Song et al, 2015 Emerging human pathogen Feltus et al, 2006;ANOFEL, 2010;Lebbad et al, 2013;Guo etal., 2015…”
Section: Wrairimentioning
confidence: 99%